2021
DOI: 10.1038/s41586-021-04187-7
|View full text |Cite
|
Sign up to set email alerts
|

Footprint evidence of early hominin locomotor diversity at Laetoli, Tanzania

Abstract: Bipedal trackways discovered in 1978 at Laetoli site G, Tanzania and dated to 3.66 million years ago are widely accepted as the oldest unequivocal evidence of obligate bipedalism in the human lineage1–3. Another trackway discovered two years earlier at nearby site A was partially excavated and attributed to a hominin, but curious affinities with bears (ursids) marginalized its importance to the paleoanthropological community, and the location of these footprints fell into obscurity3–5. In 2019, we located, exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
0
22
1
1
Order By: Relevance
“…Our results support the notion the safety ratio can be used to estimate mediolateral CoM motion from footprints in early hominins (Thompson et al, 2018), such as the Laetoli site G trackways (Tuttle et al, 1990). Another hominin footprint was found at Laetoli site A (McNutt et al, 2021), but those are ‘cross‐stepping gait‘, unfortunately, making it difficult to estimate the mediolateral CoM motion. The macaques utilized in O'Neill et al (2018) showed that the locomotor kinematics in the pelvis are similar among non‐human primates, indicating that bipedal walking in the human and chimpanzee LCA involved non‐human‐like pelvic (and presumably lower limb) motion.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the notion the safety ratio can be used to estimate mediolateral CoM motion from footprints in early hominins (Thompson et al, 2018), such as the Laetoli site G trackways (Tuttle et al, 1990). Another hominin footprint was found at Laetoli site A (McNutt et al, 2021), but those are ‘cross‐stepping gait‘, unfortunately, making it difficult to estimate the mediolateral CoM motion. The macaques utilized in O'Neill et al (2018) showed that the locomotor kinematics in the pelvis are similar among non‐human primates, indicating that bipedal walking in the human and chimpanzee LCA involved non‐human‐like pelvic (and presumably lower limb) motion.…”
Section: Discussionmentioning
confidence: 99%
“…However, these uncertainties due to intraindividual variation must be weighed because they are only valid in particular substrate conditions: loose and easily deformed sand. Even if several hominin footprints have been discovered in similar conditions, others have been left in different substrates such as clayey mud (Manolis et al, 2000, Onac et al, 2005, Citton et al, 2017, Ledoux et al, 2017 or volcanic ash (Leakey and Hay, 1979, Mietto et al, 2003, Masao et al, 2016, McNutt et al, 2021 having a lesser capacity for deformation; the footprints made in these substrates are morphologically closer to the anatomy of the foot and present a less important intraindividual dispersion.…”
Section: Intraindividual Variationmentioning
confidence: 99%
“…Hominin footprints represent a particular remain in paleoanthropology. While they were scarce in the fossil record until the 2010s (Leakey and Hay, 1979, Bennett et al, 2009, Lockley et al, 2009, they have become in the last ten years a more and more common material thanks to discoveries in all regions and for periods ranging from the Upper Miocene to the Holocene (Ashton et al, 2014, Masao et al, 2016, Gierliński et al, 2017, Ledoux et al, 2017, Altamura et al, 2018, Bustos et al, 2018, Helm et al, 2018, Duveau et al, 2019, Stewart et al, 2020, Mayoral et al, 2021, McNutt et al, 2021, Zhang et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations